An umbrella review navigating the nationwide burden of hepatitis B virus infection in Ethiopia: A call for action on vaccination, safe blood, and infection prevention - Abel Desalegn Demeke; Aboma Tsegaye; Alem Bayable; Takla Tamir; Biazin Yenealem Mekuriaw; Behailu Taye Gebremeskele; Ababo Demeke; Mesfin Abebe; Abraham Dessie Gessesse; Delelegn Emwodew Yehualashet; Habtamu Gebrie; Endris Seid Amede (PLoS ONE, 2026)
Background The Hepatitis B virus (HBV) is one of the major causes of viral hepatitis that may persist and lead to complications, including cirrhosis, hepatic decompensation, and liver cancer. Numerous systematic reviews and meta-analysis have been conducted on HBV infection among people in Ethiopia, showing inconsistent findings. This umbrella review aimed to assess the pooled prevalence of HBV infection and its associated factors among people in Ethiopia. Methods All published and unpublished systematic review and meta-analysis studies were searched on databases such as PubMed, Scopus, HINARI and Google Scholar. A measurement tool to assess systematic reviews was used for critical appraisal of the included studies. STATA software version 17 was used to conduct the analysis. I 2 test were used to determine heterogeneity, whereas funnel plots and Egger’s regression tests were used to assess publication bias. To pool the prevalence of HBV infection, a random-effects model was used and presented using a forest plot. Results Twelve systematic reviews and meta-analysis with 997,264 participants were included in this umbrella review. The pooled prevalence of the HBV infection among people in Ethiopia was 5.78% (95% CI: 5.33, 6.23). Being male, having multiple sexual partners, having a history of abortion, having body tattoos, having a history of tooth extraction, sharing sharp material, and linked to health system such as having a history of hospital admission, and blood transfusion were significant risk factors associated with HBV infection among people in Ethiopia. Conclusion This study highlights that the prevalence of HBV infection among people in Ethiopia was relatively moderate endemicity as per WHO classification. By synthesizing evidence of prior review, this study provides specific up-to-date information for clinicians and policymakers to design evidence-based public health strategies and guide future research that enable the prevention, control, and eliminate infection of HBV. PROSPERO Registration : CRD420251160887